2018
DOI: 10.1007/s00702-018-1844-x
|View full text |Cite
|
Sign up to set email alerts
|

Blood-based biomarkers predicting response to antidepressants

Abstract: Major depressive disorder is a common, serious and in some cases, life-threatening condition and affects approximately 350 million people globally. Although there is effective treatment available for it, more than 50% of the patients fail to respond to the first antidepressant they receive. The selection of a distinct treatment is still exclusively based on clinical judgment without incorporating lab-derived objective measures. However, there is growing evidence of biomarkers that it helps to improve diagnosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 189 publications
0
22
0
2
Order By: Relevance
“…Major depression is a serious disorder that has enormous consequences for the quality of life, and is one of the most prevalent forms of mental illness [ 17 ]. Patients suffered from major depression have high rates of morbidity and mortality, with profound economic and social consequences [ 18 ]. Moreover, the major depression not only affects 5% of the population, but also the numbers are increasing every year.…”
Section: Discussionmentioning
confidence: 99%
“…Major depression is a serious disorder that has enormous consequences for the quality of life, and is one of the most prevalent forms of mental illness [ 17 ]. Patients suffered from major depression have high rates of morbidity and mortality, with profound economic and social consequences [ 18 ]. Moreover, the major depression not only affects 5% of the population, but also the numbers are increasing every year.…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed a BDNF decrease and NT-3 increase levels in serum from ostomy patients when compared to healthy controls. Several studies suggest that BDNF is involved in depression 33,34 . Previous study showed that depressed patients present decreased BDNF expression, and antidepressants up-regulate the BDNF expression 35 .…”
Section: Discussionmentioning
confidence: 99%
“…As reported above, mental disorders have a modest to high heritability; also, treatment response and the appearance of adverse effects have been shown to be genetically linked. 108 111 An extensive literature covers the association of common genetic markers with the response, adverse effects, and metabolism of antidepressants and antipsychotics. 112 114 Genetic variants involved in metabolism of antidepressants or antipsychotics (CYP/CYP450 isoenzymes), drug transport ( ABCB1 ), glucocorticoid signaling ( FKBP5 ), and serotonin neurotransmission ( SLC6A4 and HTR2A ) were among those included in the first pharmacogenetic assays that have been clinically applied.…”
Section: Importance Of Genetic Environmental and Lifestyle Factorsmentioning
confidence: 99%